Maternal Microbiota, Early Life Colonization and Breast Milk Drive Immune Development in the Newborn - Kalbermatter, Cristina; Fernandez Trigo, Nerea; Christensen, Sandro; Ganal-Vonarburg, Stephanie C. (Frontiers in Immunology, 2021)
The innate immune system is the oldest protection strategy that is conserved across all organisms. Although having an unspecific action, it is the first and fastest defense mechanism against pathogens. Development of predominantly the adaptive immune system takes place after birth. However, some key components of the innate immune system evolve during the prenatal period of life, which endows the newborn with the ability to mount an immune response against pathogenic invaders directly after birth. Undoubtedly, the crosstalk between maternal immune cells, antibodies, dietary antigens, and microbial metabolites originating from the maternal microbiota are the key players in preparing the neonate’s immunity to the outer world. Birth represents the biggest substantial environmental change in life, where the newborn leaves the protective amniotic sac and is exposed for the first time to a countless variety of microbes. Colonization of all body surfaces commences, including skin, lung, and gastrointestinal tract, leading to the establishment of the commensal microbiota and the maturation of the newborn immune system, and hence lifelong health. Pregnancy, birth, and the consumption of breast milk shape the immune development in coordination with maternal and newborn microbiota. Discrepancies in these fine-tuned microbiota interactions during each developmental stage can have long-term effects on disease susceptibility, such as metabolic syndrome, childhood asthma, or autoimmune type 1 diabetes. In this review, we will give an overview of the recent studies by discussing the multifaceted emergence of the newborn innate immune development in line with the importance of maternal and early life microbiota exposure and breast milk intake.